Type II instabilities in advanced heavy water natural circulation reactors: Application to the AHWR. (November 2019) - Munoz-Cobo, J.L.; Escrivá, A.; Berna, C.
Abstract: This paper deals with the instabilities in advanced heavy water reactors driven by natural circulation at high pressure and power conditions. This paper also study which are the design and operating parameters that have more influence on the appearance of type II instabilities. Some of the results are compared with usual BWR reactors to stablish which are the differences between both types of reactors in the development of limit cycle oscillations and the maximum amplitude values of these oscillations when some of the influential parameters on the stability are changed. This paper also explains the main characteristics of the modelling used to simulate the fuel channels, the risers or outlet feeders, the recirculation loop of this reactor, and the kinetic and heat transfer models. In addition, we compare the closure relations used in this model with the experimental correlations for the AHWR, to know the applicability of the correlations for the AHWR under natural circulation conditions. Finally, we study in this paper the influence on the decay ratio (DR) and the limit cycle amplitude of a set of design and operational parameters. Some of these parameters are: the amount of coolant direct heating by neutrons and gamma-rays, the form loss coefficient at the channel inlet, the form loss coefficient in the spacers, the phase change number N p c h, the characteristic natural circulation time and the effective inertia of the recirculation loop.